Assessment of the effect of tricaine (MS-222)-induced anesthesia on brain-wide neuronal activity of zebrafish (Danio rerio) larvae - Ohnesorge, Nils; Wilzopolski, Jenny; Steinfath, Matthias; Lewejohann, Lars; Banneke, Stefanie; Heinl, Céline (Frontiers in Neuroscience, 2024)
Fast and effective anesthesia is the key for refining many invasive procedures in fish and gaining reliable data. For fish as for all vertebrates, it is also required by European law to reduce pain, suffering, and distress to the unavoidable minimum in husbandry and experiments. The most often used substance to induce anesthesia in zebrafish is tricaine (MS-222). When properly prepared and dosed, tricaine causes rapid loss of mobility, balance and reaction to touch. These signs are interpreted as a stage of deep anesthesia although its effects on the central nervous system have not convincingly been shown. Therefore, it might be possible that tricaine first acts only on the periphery, resulting in a paralyzed instead of an anesthetized fish. This has severe implications for animals undergoing procedures. To investigate the effects of tricaine on the central nervous system, we used zebrafish larvae [Tg(elavl3:H2B-GCaMP6s)] at 4 days post fertilization (dpf), expressing a calcium indicator (GCaMP6s) in all neurons, that allows monitoring and quantifying the neuronal activity. After treating larvae with 168 mg/L tricaine, a rapid loss of neuronal activity in the forebrain was observed in confocal microscopy. In contrast, only mild effects were seen in the midbrain and hindbrain. In conclusion, the different larval brain areas showed differences in the sensitivity to tricaine treatment. The effects on the central nervous system are indicative of tricaine’s anesthetic function and are consistent with behavioral observations of inactivity and unresponsiveness to touch.